Seasonal and geographical differences in aflatoxin exposures in Senegal - Watson, S.; Diedhiou, P.M.; Atehnkeng, J.; Dem, A.; Bandyopadhyay, Ranajit; Srey, C.; Routledge, M.N.; Gong, Y.Y. (Wageningen University & Research, 2015)
The aim of the study was to determine the geographical and seasonal variations in aflatoxin dietary exposure levels in adults from Senegal. A total of 168 adults (50% male) were recruited from three districts: Nioro du Rip (n=90), located in the Sudan Savannah agro-ecological zone where rainfall is sufficient for groundnut growth; Saint-Louis (n=40) and Mboro (n=38), located in the Sahel zone where groundnuts are produced under irrigated conditions. Diet information and samples were collected at groundnut harvest and post-harvest seasons. Plasma aflatoxinalbumin adducts (AF-alb) and total aflatoxin in household groundnut samples were measured by ELISA and a quantitative thin layer chromatography method, respectively. The blood AF-alb geometric mean was 45.7 pg/mg albumin (range 5.5-588.2 pg/mg). Nioro du Rip had a higher AF-alb level at harvest than Saint-Louis and Mboro (80.0 vs 15.6 and 33.3 pg/mg, P<0.001). Similar trends were observed at post-harvest (P<0.05). Seasonal trends were not consistent across the districts as Nioro du Rip had a higher AF-alb level at harvest than post-harvest (80.0 vs 58.6 pg/mg, P=0.026), whereas Saint-Louis had a higher level at post-harvest than harvest (25.6 vs 15.6 pg/mg, P=0.032). It is clear that aflatoxin exposure is prevalent in adults from Senegal and that season and geographical location are strong determinants of aflatoxin exposure.The aim of the study was to determine the geographical and seasonal variations in aflatoxin dietary exposure levels in adults from Senegal. A total of 168 adults (50% male) were recruited from three districts: Nioro du Rip (n=90), located in the Sudan Savannah agro-ecological zone where rainfall is sufficient for groundnut growth; Saint-Louis (n=40) and Mboro (n=38), located in the Sahel zone where groundnuts are produced under irrigated conditions. Diet information and samples were collected at groundnut harvest and post-harvest seasons. Plasma aflatoxinalbumin adducts (AF-alb) and total aflatoxin in household groundnut samples were measured by ELISA and a quantitative thin layer chromatography method, respectively. The blood AF-alb geometric mean was 45.7 pg/mg albumin (range 5.5-588.2 pg/mg). Nioro du Rip had a higher AF-alb level at harvest than Saint-Louis and Mboro (80.0 vs 15.6 and 33.3 pg/mg, P<0.001). Similar trends were observed at post-harvest (P<0.05). Seasonal trends were not consistent across the districts as Nioro du Rip had a higher AF-alb level at harvest than post-harvest (80.0 vs 58.6 pg/mg, P=0.026), whereas Saint-Louis had a higher level at post-harvest than harvest (25.6 vs 15.6 pg/mg, P=0.032). It is clear that aflatoxin exposure is prevalent in adults from Senegal and that season and geographical location are strong determinants of aflatoxin exposure.